Balanced diet and its impact on blood pressure and blood sugar in type 2 diabetes: a socio-behavioral literature review - Farida Anwari; Ananta Citra; Acivrida Mega Charisma; Arista Wahyu Ningsih; Adinugraha Amarullah; Martina Kurnia Rohmah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Type 2 diabetes mellitus (T2DM) represents a major global health burden, characterized by insulin resistance, chronic hyperglycemia, and a high risk of cardiovascular complications. Among various modifiable risk factors, dietary patterns play a central role in regulating both glycemic control and blood pressure. This literature review explores the impact of balanced diets—particularly the Mediterranean diet, the Dietary Approaches to Stop Hypertension (DASH) diet, and plant-based diets—on metabolic outcomes in T2DM while integrating socio-behavioral perspectives. The review employed a qualitative literature review approach, systematically analyzing peer-reviewed studies published within the last five years from databases such as PubMed, Scopus, and Google Scholar. Content analysis was used to identify recurring themes, evaluate consistency across findings, and compare both physiological and behavioral aspects of dietary adherence. Findings consistently demonstrate that balanced diets significantly improve HbA1c levels, enhance insulin sensitivity, and lower systolic and diastolic blood pressure in T2DM patients. Among dietary models, the Mediterranean diet shows the strongest evidence for metabolic benefits, followed closely by DASH. However, dietary adherence is profoundly shaped by socio-behavioral determinants including cultural eating practices, family support, economic constraints, and patient motivation. Technological interventions, such as mobile health applications, offer promising strategies to strengthen adherence, although accessibility issues remain. In conclusion, balanced dietary interventions are effective non-pharmacological strategies for T2DM management but require socio-behavioral integration to achieve sustainable outcomes. Future programs must combine nutritional education with cultural adaptation, behavioral reinforcement, and equitable access to healthy foods.